Exocrine pancreatic and enterocyte function in patients with advanced pancreatic cancer. Issue 6 (December 2019) - Witvliet-van Nierop, J.E.; de van der Schueren, M.A.E.; Scheffer, H.J.; Vroomen, L.G.; Meijerink, M.R.; van Bodegraven, A.A.; Wierdsma, N.J.
Summary: Background & aims: Exocrine pancreatic function is affected in patients with locally advanced pancreatic cancer (LAPC), clinically leading to steatorrhea. It is unknown whether maldigestion and malabsorption can also be attributed to impaired intestinal enterocyte function. In this exploratory study enterocyte function was assessed in patients with locally advanced pancreatic cancer, treated with Irreversible Electroporation (IRE). Methods: Enterocyte function was studied by Citrulline Generation Test (CGT). Intestinal absorption capacity of energy and fat was calculated from the differences between nutritional intake (four-days diary) and quantified fecal losses energy and fat in three-days feces collection. Results: Twelve patients were included before IRE, and 5 patients had follow-up measurements. Fasted citrulline [CIT] and glutamine [GLU] levels were below reference levels of healthy subjects ([CIT] 38 ± 8 μmol/L; [GLU] 561 ± 77 μmol/L) both before ([CIT] 25 ± 9 μmol/L; [GLU] 65 ± 35 μmol/L) and after IRE ([CIT] 19 ± 9 μmol/L; [GLU] 53 ± 26 μmol/L) whereas CGT curves were normal, indicating normal enterocyte function (slope 0.21 ± 0.12 and 0.17 ± 0.07 μmol/L/min; [CIT] increment 63 ± 39 and 80 ± 44% respectively). Severe energy/fat malabsorption was present in 6 out of 12 patients with LAPC (mean loss 349 kcal/d, 13 g fat/d) before and in 4 out of 5 patients (mean loss 509 kcal/d, 32 g fat/d) after IRE respectively. Conclusions: Enterocyte function was generally within reference limits in patients with advanced pancreatic cancer. Severe malabsorption may be explained by exocrine pancreatic insufficiency.